1981
DOI: 10.1128/aem.41.6.1475-1478.1981
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio cholerae Isolated from Oysters

Abstract: Of 790 samples of oyster shellstock freshly harvested during a 12-month survey, 111 (most of which were harvested from June through August) contained Vibrio cholerae non-Ol (611 strains), and seven contained 01 Inaba (11 strains) organisms. None of the V. cholerae strains isolated were enterotoxigenic by immunological and biological tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Non-O1 strains are much more commonly isolated from the environment than are O1 strains, even in epidemic settings in which fecal contamination of the environment might be expected. Outside of epidemic areas (and away from areas that may have been contaminated by cholera patients), O1 environmental isolates are almost always CT negative (285,304,375,464). However, it is clear that CT-producing V. cholerae O1 can persist in the environment in the absence of known human disease (78,396,478).…”
Section: Reservoirsmentioning
confidence: 99%
“…Non-O1 strains are much more commonly isolated from the environment than are O1 strains, even in epidemic settings in which fecal contamination of the environment might be expected. Outside of epidemic areas (and away from areas that may have been contaminated by cholera patients), O1 environmental isolates are almost always CT negative (285,304,375,464). However, it is clear that CT-producing V. cholerae O1 can persist in the environment in the absence of known human disease (78,396,478).…”
Section: Reservoirsmentioning
confidence: 99%
“…V. cholerae that do not belong to the O1 serogroup, collectively referred to as non-O1 V. cholerae, are ubiquitous residents of aquatic environs [1,2]. In contrast, the isolation of 'culturable' V. cholerae belonging to the O1 serogroup from the environment are few and far between, and those that have been isolated are invariably non-toxigenic [3]. The incidence of 'culturable' toxigenic V. cholerae O1 in aquatic environs coincides with the incidence of active cholera cases in the vicinity or during periods of epidemics [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth investigating, from the standpoint of public health and food hygiene, CT producing activity of non-O I V. cholerae isolated from various sources. Twedt et al (16), using radioimmunoassay, reported that none of 486 strains isolated from oysters produced CT-like-enterotoxin.…”
Section: Discussionmentioning
confidence: 99%